Tadalafil Modulates Intracerebroventricular Streptozotocin-Induced Cognition and Memory Impairment in the Young and Middle-Aged Rats - Siamak Shahidi; Masoumeh Asadbegi; Nasrin Hashemi-Firouzi; Alireza Komaki; Minoo Mahmoodi (Tabriz University of Medical Sciences, 2021)
Background: Learning and memory may decline due to Alzheimer's disease (AD) in older adults. A reduction in cyclic guanosine monophosphate concentration and an increase in phosphodiesterase activity have been reported in the process of aging. Althoughphosphodiesterase (PDE) type 5 inhibitor, Tadalafil is used to treat erectile dysfunction; PDE inhibitors possibly prevent cognition impairment in aging. This study was designed to investigate the effects of tadalafil on memory in middle-aged and young healthy and AD rats. Methods: Memory impairment was induced by intracerebroventricular (ICV) administration of streptozotocin (STZ; 3 mg/kg) in AD rats. Male Wistar rats (middle-aged and young) were distributed into six groups as follows: two control, two AD, and two AD+tadalafil (1 mg/kg)groups. Saline or tadalafil was administered once a day orally for 40 consecutive days. Animals were tested using novel object recognition (NOR), passive avoidance learning (PAL), and Morris water maze (MWM) tests. Results: Aged AD rats exhibited a significant impairment in cognition in the NOR test and impaired learning and memory in PAL and MWM tests compared with the control aged rats. Tadalafil treatment in aged AD rats significantly improved the discrimination index in the NORtest, decreased the time spent in the dark compartment in the PAL test, and increased time spent in the target quadrant in MWM tests compared with aged AD rats. In young AD rats, treatment with tadalafil significantly enhanced cognition, learning, and memory in the NOR, PAL, andMWM tests compared with young AD rats treated with saline. Conclusion: Tadalafil treatment in aged rats improves cognition and memory after STZ-induced(ICV) memory impairment. It can be concluded that chronic treatment with tadalafil is protective against cognitive, learning, and memory impairment in both young and aged subjects.